The Effect of Milk or its Combination with Tea and 0.2% NaF on Dental Enamel Demineralization Analyzed by Micro Computed Tomography - Rahardjo, Anton; Sahertian, Raisa D.; Ramadhani, Siti A.; Maharani, Diah A.; Latief, Fourier DE. (UI Scholars Hub, 2014)
Fluoride and calcium play an important role in the prevention of dental caries, promoting the inhibition of demineralization and the increase of remineralization. Objective: To investigate the effects of milk with/without the combination of tea and 0.2% NaF on enamel demineralization using micro-computed tomography (microCT). Methods: The coronal parts of 40 extracted sound premolars were prepared as tooth blocks. An unvarnished occlusal surface window was created for each tooth by covering the occlusal surface with a 3x5 mm2 sticker and painting all other surfaces with an acid-resistant varnish. These blocks were randomly allocated into four groups that were immersed in remineralizing solutions for 26 minutes: Group A, milk; Group B, milk and tea; Group C, milk and 0.2% NaF; and Group D, deionized water (control). Results: After 3 days of immersion in a buffered demineralization solution at pH 4.4, micro-CT scans were taken. The mean grayscale values and the standard deviations are: 98.1 ± 24.0; 90.8 ± 9.1; 92.6 ± 21.4; 81.1 ± 20.3, respectively. The mean grayscale values were significantly different among the four groups (p